پێگەی تەلەڤزیۆن لە گەشە پێدانی هۆشیاری ژینگەیی لە هەرێمی کوردستاندا (خوێندكارانی زانكۆ بەنموونە) - حسن, پ.د هێمن مجید; حسن, ژیان هادی (Sulaimani Journal for Humanities, 2023)
This Research Deals with a Serious Societal Issue on The Grounds of The Common Good. Developmental Processes and Environmental Awareness Are Very Important Processes for The Continuity Of life. The aim of the Study Is to Know the Position of Television channels in Developing Environmental Awareness in The Kurdistan Region in Communicating What This Concept Means and Aims, As Well As the Methods Used to Achieve This. Also, This Research Is Considered One of The Descriptive Researches That Are Appropriate to Understand the Details Of its Main Pillars, Using the Survey as a Method Through the Questionnaire Tool.One of The Most Important Finding of This Research Is That Television Channels Have Sometimes Played Their Role in Developing Environmental Awareness, But They Were Unable to Participate in The Development of Environmental Awareness In The Kurdistan Region As Necessary And On An Ongoing Basis.